The wolf from Grotta Mora Cavorso (Simbruini mountains, Latium) within the evolution of Canis lupus L., 1758 in the Quaternary of Italy - Salari L.; Achino K. F.; Gatta M.; Petronio C.; Rolfo M. F.; Silvestri L.; Pandolfi L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
This paper describes the Late Pleistocene and Holocene remains of Canis lupus from Grotta Mora Cavorso (Latium, Italy), with a particular focus on the anatomically connected skeleton found in Layer 7, radiometrically dated to over 43,500years BP and correlated with Marine Isotopic Stage 3. The studied specimens were compared with wolf remains collected from numerous Middle and Late Pleistocene and Holocene sites in Italy, France, Austria and Slovenia. Additional comparisons were made with a sample of the extant Apennine wolf, Canis lupus italicus. The Late Pleistocene and Holocene wolves from Grotta Mora Cavorso range between 6 and 10years of age at death, 64–75cm in height at the withers, 150–162cm in body length, and 30–39kg in body mass. They are morphometrically close to Canis lupus maximus, a Late Pleistocene chrono-subspecies of France. The late Middle and Late Pleistocene wolves of Italy show a great variability in body size. This prevents the recognition of a progressive increase of size in Italian wolves with any resulting biochronological implications. The Holocene reduction in body size of the extant Apennine wolf was more recent than previously thought, probably because of genetic isolation, and the rarefaction and subsequent local extinction of large-sized prey, such as red deer. In addition, the 6year old anatomically connected specimen discovered at Grotta Mora Cavorso, probably a female, allows some considerations on the functional morphology of Pleistocene wolves.